Unequal distribution of genetically-intact HIV-1 proviruses in cells expressing the immune checkpoint markers PD-1 and/or CTLA-4 - Fisher, Katie; Schlub, Timothy E.; Boyer, Zoe; Rasmussen, Thomas A.; Rhodes, Ajantha; Hoh, Rebecca; Hecht, Frederick M.; Deeks, Steven G.; Lewin, Sharon R.; Palmer, Sarah (Frontiers in Immunology, 2023)
HIV-1 persists in resting CD4+ T-cells despite antiretroviral therapy (ART). Determining the cell surface markers that enrich for genetically-intact HIV-1 genomes is vital in developing targeted curative strategies. Previous studies have found that HIV-1 proviral DNA is enriched in CD4+ T-cells expressing the immune checkpoint markers programmed cell death protein-1 (PD-1) or cytotoxic T-lymphocyte associated protein-4 (CTLA-4). There has also been some success in blocking these markers in an effort to reverse HIV-1 latency. However, it remains unclear whether cells expressing PD-1 and/or CTLA-4 are enriched for genetically-intact, and potentially replication-competent, HIV-1 genomes. We obtained peripheral blood from 16 HIV-1-infected participants, and paired lymph node from four of these participants, during effective ART. Memory CD4+ T-cells from either site were sorted into four populations: PD-1-CTLA-4- (double negative, DN), PD-1+CTLA-4- (PD-1+), PD-1-CTLA-4+ (CTLA-4+) and PD-1+CTLA-4+ (double positive, DP). We performed an exploratory study using the full-length individual proviral sequencing (FLIPS) assay to identify genetically-intact and defective genomes from each subset, as well as HIV-1 genomes with specific intact open reading frames (ORFs). In peripheral blood, we observed that proviruses found within PD-1+ cells are more likely to have intact ORFs for genes such as tat, rev and nef compared to DN, CTLA-4+ and DP cells, all of which may contribute to HIV-1 persistence. Conversely, we observed that CTLA-4 expression is a marker for cells harbouring HIV-1 provirus that is more likely to be defective, containing low levels of these intact ORFs. In the lymph node, we found evidence that CTLA-4+ cells contain lower levels of HIV-1 provirus compared to the other cell subsets. Importantly, however, we observed significant participant variation in the enrichment of HIV-1 proviruses with intact genomes or specific intact ORFs across these memory CD4+ T-cell subsets, and therefore consideration of additional cellular markers will likely be needed to consistently identify cells harbouring latent, and potentially replication-competent, HIV-1.